Repeat Guests’ Perception about New Facilities and Increased Price at Padma Hotel Bandung - Nasution, Reza Ashari; Wiradiputra, Andika (School of Business and Management Institut Teknologi Bandung, 2010)
In 2009 after one and a half year closed for reconstruction, Malya Hotel Bandung renewed,reopened, rebranded with new name Padma Hotel Bandung. The changes are not only aboutthe name but also the logo, the concept, the grade, and the facilities inside and outside room.This results in higher price to customers. At the opening, Padma Hotel Bandung has focusedtheir marketing promotion on Malya repeat guest . The management concerns about theguests’ perception about the additional price because they will be the main visitors to thehotel. Survey was conducted and the findings reveal that the guests’ perception about theoverall inside and outside room is really good. They agreed that Padma Hotel Bandung hasprovided better facilities compared to Malya Hotel. Some facilities have been identified toinfluence customers’ perception about the overall perception about new facilities. Related tothe increased price, the answer quite varies. The repeat guests stated their doubt about thefairness of the price. Even though, they wanted to come back due to emotional benefitscustomers can get from the new Padma Hotel.Key words: repeat customer, rebranding, customer perception, repurchase intention, servicemarketing